Layanan Informasi dengan Media Brosur untuk Meningkatkan Pemahaman Karier Siswa - Titik Nur Wulandari; Yansen Alberth Reba (Universitas Cenderawasih, 2022)
This study aimed to determine the effectiveness of information services through brochure media to improve students' career understanding. It applied a quantitative approach with pre-experimental research method. Then, the researcher used a one-group pretest-posttest design. The research population was students of class XII IPA1 & XII IPA2 of SMA Muhammadiyah Jayapura City, totaling 60 students from 2 classes. The research sample was the total sample because the number was less than 100. Based on the previous statistical data obtained from the pre-test and post-test data, there was a significant increase between the initial pre-test and the final post-test. In the pre-test data, it obtained an average of 74.79 which was included in the medium category. Then, after giving treatment of information services through brochure media, it obtained post-test data with an average of 84.48 which was included in the high category. Thus, the increase in students' career understanding from pre-test to post-test increased by 9.35. Based on the previous statistical test data, it obtained a (z) value of 6.684. Then, Asymp. Sig. (2-tailed) showed 0.000 which meant significant. This indicated that information service using brochure media was effective in increasing students' career understanding.